Laparoscopic resection of a gastrointestinal stromal tumour located in stomach - Erzin, Yusuf; Karataş, Adem; Paksoy, Melih; Velibeyoğlu, Fatih; Doğusoy, Gülen; Tuncer, Murat (Cerrahpaşa Medical Journal, 2014)
Gastrointestinal tumors (GISTs) represent the largest category of nonepithelial neoplasms of the gastrointestinal tract. They arise from the neoplastic degeneration of primitive mesenchymal cells and demonstrate considerable variability in their differentiation pathways. GISTs can occur in all segments of the intestine mostly occuring in the stomach and small intestine. The clinical course of GISTs is heterogeneous and the most important prognostic factors are tumor size, mitotic count, and the presence of c-kit gene mutation. Here we report a case with a huge GIST, finally resected laparoscopically, which presented with melena and a polypoid mass measuring 3cmx3cm during upper gastrointestinal endoscopy.